2008
DOI: 10.1111/j.1553-2712.2007.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

TASER X26 Discharges in Swine Produce Potentially Fatal Ventricular Arrhythmias

Abstract: Objectives: Data from the authors and others suggest that TASER X26 stun devices can acutely alter cardiac function in swine. The authors hypothesized that TASER discharges degrade cardiac performance through a mechanism not involving concurrent acidosis.Methods: Using an Institutional Animal Care and Use Committee (IACUC)-approved protocol, Yorkshire pigs (25-71 kg) were anesthetized, paralyzed with succinylcholine (SCh; 2 mg ⁄ kg), and then exposed to two 40-second discharges from a TASER X26 with a transcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 26 publications
3
55
3
1
Order By: Relevance
“…25 It is clear from the information cited above that an ECD shock to the chest can produce cardiac electrical capture at rapid rates in animals and humans. [11][12][13][14][15][16][17][18] Furthermore, it is clear that VF has been documented as early as 2 minutes after an ECD shock to humans. 3,5 What is lacking is the actual ECG recording of VF induction during an ECD shock in humans, a practical impossibility unless it fortuitously occurred in an individual with a recording device already in place.…”
Section: Proposed Mechanism Of Ecd-induced Sudden Cardiac Arrestmentioning
confidence: 99%
See 3 more Smart Citations
“…25 It is clear from the information cited above that an ECD shock to the chest can produce cardiac electrical capture at rapid rates in animals and humans. [11][12][13][14][15][16][17][18] Furthermore, it is clear that VF has been documented as early as 2 minutes after an ECD shock to humans. 3,5 What is lacking is the actual ECG recording of VF induction during an ECD shock in humans, a practical impossibility unless it fortuitously occurred in an individual with a recording device already in place.…”
Section: Proposed Mechanism Of Ecd-induced Sudden Cardiac Arrestmentioning
confidence: 99%
“…20 In addition to the importance of probe location, longerduration shocks at normal TASER X26 outputs appear more likely to induce VF. 13,14 Although it is possible that body size might influence cardiac capture and development of VF, clearly big people can still develop VF from an ECD shock (see the Table).…”
Section: Animal and Clinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…youtube.com/watch?v=PxcXwk4UHm4). The second study 16 showed that succinylcholine eliminated the acidosis after the If our data can be translated to humans, then ventricular rhythm may be captured and postdischarge dysrhythmias or VF may occur. Such transcardiac vectors should be avoided when possible and the potential for deterioration of the cardiac rhythm to VF in the field should be considered….Users should be trained to recognize the possible cardiac effects and be prepared to use automated external defibrillators and cardiopulmonary resuscitation maneuvers when needed.…”
Section: Animal Researchmentioning
confidence: 99%